Fecal Serine Protease Profiling in Inflammatory Bowel Diseases - Jablaoui, Amin; Kriaa, Aicha; Mkaouar, Héla; Akermi, Nizar; Soussou, Souha; Wysocka, Magdalena; Wołoszyn, Dominika; Amouri, Ali; Gargouri, Ali; Maguin, Emmanuelle; Lesner, Adam; Rhimi, Moez (Frontiers in Cellular and Infection Microbiology, 2020)
Serine proteases are extensively known to play key roles in many physiological processes. However, their dysregulation is often associated to several diseases including inflammatory bowel diseases (IBD). Here, we used specific substrates to monitor fecal protease activities in a large cohort of healthy and IBD patients. Of interest, serine protease activity was 10-fold higher in IBD fecal samples compared to healthy controls. Moreover, functional analysis of these fecal proteolytic activities revealed that the most increased activities are trypsin-like, elastase-like and cathepsin G-like. We also show for the first time, an increase of proteinase 3-like activity in these samples compared to controls. Results presented here will guide further investigations to better understand the relevance of these peptidases in IBD.